Study of Seedling Growth of Radish Seed Using Dielectric Barrier Discharge at Atmospheric Pressure - Mishra, L. N.; Sapkota, R. K.; Shah, A. K.; Shrestha, R. (Patan Pragya, 2023)
This work deals with the evaluation of effects of period of plasma treatment on radish seeds. The parameters such as germination rate (2nd to 9th day), shoot length (5th to 25th day), root length (8th to 12th day), and leaf area (measured for a duration of 12 days) were observed and analyzed. It is revealed that the untreated seeds exhibited the lowest values for all growth parameters whereas there was a significant improvement in germination rate, shoot length, root length, and leaf area after the increment of treatment duration. Experimentally, it is observed that those parameters such as germination rate, shoot length, root length, and leaf area become optimum at a treatment duration of 3 minutes and 30 seconds. This indicates that the plasma treatment using the DBD method has a positive impact on the seedling growth of radish plants, enhancing their overall development and vigor. This work could be useful in agriculture farming for the enhancement of the yielding growth.